RATIONALE FOR THE SELECTION OF INNOVATIVE MATERIALS BASED ON THE COST OF THE LIFE CYCLE OF THE GAS PIPELINE - A. Afanasyev; E. Ermolaev; E. Acri (Вестник университета)
The present study is devoted to the selection of innovative materials based on their life cycle of the gas pipeline. Assessment of the efficiency of laying gas pipelines is currently carried out only from the position of construction and installation works and does not take into account the interests of organizations that provide their maintenance and major repairs. Increasing the efficiency of gas supply projects is possible only if the interests of all participants in the construction of the gas pipeline, its maintenance and overhaul are observed. With such a statement of the question, the rationale for choosing innovative materials requires a new approach, which justifies the relevance of this article. The method of calculating the cost of the life cycle of a gas pipeline and periods of the object's life cycle are considered. The averaged costs over the life cycle of the object are given. A method for selecting an economically viable option for using pipes for a gas pipeline is proposed. An algorithm for calculating the cost of the life cycle of a gas pipeline is given.